Immune checkpoint inhibitors for the treatment of solid tumors in HIV-infected patients: is it worth the risk? - E. A. Degtiareva; S. A. Protsenko; E. N. Imyanitov (Сибирский онкологический журнал)
Objective. To present the available data regarding the tolerance of immune checkpoint inhibitors (ICIs) in cancer patients with concurrent HIV.Material and Methods. A literature search was conducted in the electronic databases PubMed, Cochrane Library and UpToDate up to February 2022.Results. The article outlines the background and experience of using ICIs for the treatment of malignant tumors in patients with concomitant HIV infection.Conclusions. Until recently, the presence of chronic infections, including HIV infection, was one of the key contraindications for prescribing immunotherapy. However, the recent scientific publications demonstrate the efficacy and good tolerability of ICIs in cancer patients with concurrent HIV. Future prospective clinical trials will help to predetermine the potential of immunotherapy in clinical practice in this patients.